2012
DOI: 10.1371/journal.pone.0031834
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Polychlorinated Biphenyls in Adipocytes: Selective Targeting to Lipid Droplets and Role of Caveolin-1

Abstract: BackgroundPolychlorinated biphenyls (PCBs) are persistent environmental pollutants that preferentially accumulate in lipid-rich tissues of contaminated organisms. Although the adipose tissue constitutes a major intern reservoir of PCBs and recent epidemiological studies associate PCBs to the development of obesity and its related disorders, little is known about the mechanisms involved in their uptake by the adipose tissue and their intracellular localization in fat cells.Methodology/Principal FindingsWe have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…These limits are fixed to protect consumer health from exposure to foods containing PCBs. Experimental studies have been mainly performed to evaluate the accumulation dynamics, storage and release in/from adipose cells of NDL-PCBs (Bourez et al, 2012(Bourez et al, , 2013Gallenberg and Vodicnik, 1987).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…These limits are fixed to protect consumer health from exposure to foods containing PCBs. Experimental studies have been mainly performed to evaluate the accumulation dynamics, storage and release in/from adipose cells of NDL-PCBs (Bourez et al, 2012(Bourez et al, , 2013Gallenberg and Vodicnik, 1987).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…We observed that fetal fibroblasts and amniocytes responded differently to PCB exposure probably because of their different roles into the organism and their different biological features, such as lipid content. PCBs possess high lipophilic properties (Yu and Mylander, 2011) and can accumulate mainly in cells with high lipid content (Müllerová and Kopecký, 2007;Bourez et al, 2012). In this regard, the literature reveals a lower degree of PCBs accumulation in the amniotic fluids compared to other biological compartments, such as Table 2 Frequency of chromosomal abnormalities in SEF.…”
Section: Discussionmentioning
confidence: 99%
“…The PCBs were added to the culture medium as ethanolic solution and four conditions of PCB contamination were tested: ( i ) 2,4,4′-trichlorobiphenyl (PCB-28); ( ii ) 2,3′,4,4′,5-pentachlorobiphenyl (PCB-118); ( iii ) 2,2′,4,4′,5,5′-hexachlorobiphenyl (PCB-153); ( iv ) an equimolar mixture of three PCB congeners (PCB-28, -118 and -153), also called cocktail of PCBs. In all conditions of contamination, each PCB was added to the culture medium at a concentration of 300 nM, which is within the range of concentrations found in in vivo and in vitro studies [4], [29], [30]. Impact of the ethanol vehicle was tested earlier [4].…”
Section: Methodsmentioning
confidence: 99%
“…In all conditions of contamination, each PCB was added to the culture medium at a concentration of 300 nM, which is within the range of concentrations found in in vivo and in vitro studies [4], [29], [30]. Impact of the ethanol vehicle was tested earlier [4].…”
Section: Methodsmentioning
confidence: 99%